2001
DOI: 10.1162/105474601750216812
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Visual Path Integration in VEs

Abstract: When moving around in the world, humans can use the motion sensations provided by their kinesthetic, vestibular, and visual senses to maintain their sense of direction. Previous research in virtual environments (VEs) has shown that this socalled path integration process is inaccurate in the case that only visual motion stimuli are present, which may lead to disorientation. In an experiment, we investigated whether participants can calibrate this visual path integration process for rotations; in other words, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…This argues against the usage of HMDs and any display with rather limited FOV for applications involving simulated movements of the observer. This supports results from other studies that found similar drawbacks and considerable systematic errors when using HMDs for executing simulated self-rotations [Bakker et al 1999[Bakker et al , 2001Riecke et al 2005] as well as for simple navigation tasks [Kearns et al 2002]. This might also explain the small performance differences observed between the real-world and HMD condition of the main experiment.…”
Section: Control Experimentssupporting
confidence: 90%
See 1 more Smart Citation
“…This argues against the usage of HMDs and any display with rather limited FOV for applications involving simulated movements of the observer. This supports results from other studies that found similar drawbacks and considerable systematic errors when using HMDs for executing simulated self-rotations [Bakker et al 1999[Bakker et al , 2001Riecke et al 2005] as well as for simple navigation tasks [Kearns et al 2002]. This might also explain the small performance differences observed between the real-world and HMD condition of the main experiment.…”
Section: Control Experimentssupporting
confidence: 90%
“…Further drawbacks associated with HMDs include distortions of the perceived space, as well as impaired spatial orientation performance [Arthur 2000;Bakker et al 1999Bakker et al , 2001Creem-Regehr et al 2003;Hettinger et al 1996;Kearns et al 2002;Nelson et al 1998;Riecke et al 2005]. The whole projection setup is mounted on top of the motion platform [see Figure 7(d)] in order to allow for optimal viewing conditions and immersion.…”
mentioning
confidence: 99%
“…Participants were asked to reproduce distances traveled and to execute ego-rotations for given angles in a simple virtual environment without any landmarks * . The experiment was similar to the translation experiments by Bremmer and Lappe (1999) 11 and the rotation experiments by Bakker et al (1999Bakker et al ( , 2001), 1, 2 respectively, but a different VR setup involving a half-cylindrical 180 • projection screen with three projectors was used instead of a flat projection screen (90 • ×90 • ) and HMD, respectively.…”
Section: Experiments 1 -Turn Execution and Distance Reproduction Usingmentioning
confidence: 93%
“…[1][2][3][4][5][6]13 Rather, presenting optic flow on a half-cylindrical projection screen allowed participants to perform simulated ego-rotation with amazing accuracy and precision. Both systematic errors and turning variability were typically less than 5%, without any feedback training.…”
Section: Turn Executionmentioning
confidence: 99%
“…Virtual environments can be more complex than natural environments with respect to their scale [4,2], structural complexity and dimensionality [5]. Furthermore, virtual environments often differ from natural environments with respect to the sensory modalities involved, depending on the use of visual, auditory and vestibular displays [6,7,8,9,10,11] and interaction methods [8]. Thus, an optimal support of human spatial navigation in virtual environments relies on knowing the effects of involving multiple sensory modalities.…”
Section: Introductionmentioning
confidence: 99%